2010
DOI: 10.1038/nm.2125
|View full text |Cite
|
Sign up to set email alerts
|

Slitrk5 deficiency impairs corticostriatal circuitry and leads to obsessive-compulsive–like behaviors in mice

Abstract: Obsessive-compulsive disorder (OCD) is a common psychiatric disorder defined by the presence of obsessive thoughts and repetitive compulsive actions, and it often encompasses anxiety and depressive symptoms1,2. Recently, the corticostriatal circuitry has been implicated in the pathogenesis of OCD3,4. However, the etiology, pathophysiology and molecular basis of OCD remain unknown. Several studies indicate that the pathogenesis of OCD has a genetic component5–8. Here we demonstrate that loss of a neuron-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
316
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(338 citation statements)
references
References 37 publications
13
316
2
1
Order By: Relevance
“…Mutation of this serine residue to alanine was shown to abolish the interaction of Slitrk1 with 14-3-3 proteins, and block the induction of neurite outgrowth in cultured mouse neurons (Kajiwara et al, 2009). Studies using knockout mice have implicated Slitrk5 in the dendritic complexity of medium spiny neurons of the adult striatum (Shmelkov et al, 2010), and showed that Slitrk6 exerts trophic actions (Katayama et al, 2009). Slitrk6-knockout mice also exhibit marked cell death in the spiral and vestibular ganglia (Katayama et al, 2009).…”
Section: Slit and Trk-like Familymentioning
confidence: 99%
See 4 more Smart Citations
“…Mutation of this serine residue to alanine was shown to abolish the interaction of Slitrk1 with 14-3-3 proteins, and block the induction of neurite outgrowth in cultured mouse neurons (Kajiwara et al, 2009). Studies using knockout mice have implicated Slitrk5 in the dendritic complexity of medium spiny neurons of the adult striatum (Shmelkov et al, 2010), and showed that Slitrk6 exerts trophic actions (Katayama et al, 2009). Slitrk6-knockout mice also exhibit marked cell death in the spiral and vestibular ganglia (Katayama et al, 2009).…”
Section: Slit and Trk-like Familymentioning
confidence: 99%
“…Knockout mice have also been used recently to demonstrate the involvement of Slitrk3 and -5 in synapse formation (Shmelkov et al, 2010;Takahashi et al, 2012). In cultured neurons, Slitrk5 localizes to postsynaptic sites.…”
Section: Slit and Trk-like Familymentioning
confidence: 99%
See 3 more Smart Citations